Linkage of Marine Bacterial Polyunsaturated Fatty Acid and Long-Chain Hydrocarbon Biosynthesis - Allemann, Marco N.; Shulse, Christine N.; Allen, Eric E. (Frontiers in Microbiology, 2019)
Various marine gamma-proteobacteria produce omega-3 polyunsaturated fatty acids, such as eicosapentaenoic acid (20:5, EPA) and docosahexaenoic acid (22:6, DHA), which are incorporated into membrane phospholipids. Five genes, designated pfaABCDE, encode the polyketide/fatty acid synthase necessary for production of these long-chain fatty acids. In addition to de novo biosynthesis of EPA and DHA, the “Pfa synthase” is also involved with production of a long-chain polyunsaturated hydrocarbon product (31:9, PUHC) in conjunction with the oleABCD hydrocarbon biosynthesis pathway. In this work, we demonstrate that OleA mediates the linkage between these two pathways in vivo. Co-expression of pfaA-E along with oleA from Shewanella pealeana in Escherichia coli yielded the expected product, a 31:8 ketone along with a dramatic ~10-fold reduction in EPA content. The decrease in EPA content was independent of 31:8 ketone production as co-expression of an OleA active site mutant also led to identical decreases in EPA content. We also demonstrate that a gene linked with either pfa and/or ole operons in diverse bacterial lineages, herein designated pfaT, plays an accessory role in maintaining optimal production of Pfa synthase derived products in Photobacterium and Shewanella species.